A Web-Based Patient Tool for Preventive Health - Shantanu Nundy; Mosmi Surati; Ifeoma Nwadei; Gaurav Singal; Monica E. Peek (SAGE Publishing, 2012)
Background: The Internet is a promising medium for engaging the community in preventive care and health promotion, particularly among those who do not routinely access health care. Objective: The authors pilot-tested a novel website that translates evidence-based preventive health guidelines into a patient health education tool. The web-based tool allows individuals to enter their health risk factors and receive a tailored checklist of recommended preventive health services based on up-to-date guidelines from the US Preventive Services Task Force and the Advisory Committee on Immunization Practices. Methods: The authors conducted surveys and in-depth interviews among a purposive sample of adults from an urban African American community who pilot-tested the website in a standardized setting. Interviews were designed to assess the usability, navigability, and content of the website and capture patient perceptions about its educational value and usefulness. Each interview was audiotaped, transcribed, and examined using the constant comparative method. Results: Twenty-five participants piloted the tool: 96% found it easy to use and 64% reported learning something new. Many participants reported that, in addition to improving clinical preventive care (the intended purpose), the website could serve as a stand-alone tool to improve self-awareness and motivate behavior change. Conclusions: A web-based tool designed to translate preventive health guidelines for the community may serve the dual purpose of improving the delivery of preventive health care and encouraging health promotion. The website developed here is publicly available for use by practitioners and the community.